1995
DOI: 10.1074/jbc.270.46.27646
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipopolysaccharide Biosynthesis and Cell Growth following Inactivation of the kdtA Gene in Escherichia coli

Abstract: The enzyme 3-deoxy-D-manno-octulosonic acid (Kdo) transferase is encoded by the kdtA gene in Escherichia coli. The enzyme is a single polypeptide that catalyzes the transfer of two Kdo residues to a tetraacyldisaccharide-1,4'-bisphosphate precursor of lipid A, designated lipid IVA (Belunis, C.J., and Raetz, C.R.H. (1992) J. Biol. Chem. 267, 9988-9997). To determine if Kdo transfer to lipid IVA is required for growth, we constructed a strain of E. coli with a chromosomal kdtA::kan insertion mutation. In mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 29 publications
9
135
0
Order By: Relevance
“…The essential role of Kdo was first established by the characterization of Salmonella mutants conditionally blocked in the biosynthesis of this sugar acid (Rick and Osborn, 1977). Recently, Belunis et al (1995) confirmed this data with a temperature-sensitive knockout system for the Kdo transferase of Escherichia coli. Based on these findings, the enzymes involved in the biosynthesis and activation of Kdo evoked increasing interest as potential targets for new types of antibiotics with broad reactivity against all gram-negative bacteria (Goldman et al, 1987;Hammond et al, 1987).…”
supporting
confidence: 65%
“…The essential role of Kdo was first established by the characterization of Salmonella mutants conditionally blocked in the biosynthesis of this sugar acid (Rick and Osborn, 1977). Recently, Belunis et al (1995) confirmed this data with a temperature-sensitive knockout system for the Kdo transferase of Escherichia coli. Based on these findings, the enzymes involved in the biosynthesis and activation of Kdo evoked increasing interest as potential targets for new types of antibiotics with broad reactivity against all gram-negative bacteria (Goldman et al, 1987;Hammond et al, 1987).…”
supporting
confidence: 65%
“…Furthermore, the E. coli Kdo transferase (KdtA) (34,35) requires the presence of an unsubstituted 4Ј-phosphate moiety in its acceptor substrates, 2 consistent with the idea that incorporation of the L-Ara4N moiety at the 4Ј-phosphate position occurs later than Kdo addition during normal lipopolysaccharide biosynthesis. Conversely, given the structures of lipid A precursors in Kdodeficient mutants of S. typhimurium in which the pEtN substituent occurs solely at the 4Ј-position (6,19), it appears that pEtN addition to the 1-phosphate must also be Kdo-dependent, whereas pEtN transfer to the 4Ј-phosphate is not.…”
Section: Discussionmentioning
confidence: 76%
“…Galactosyltransferase reactions were identical but also included 1.0 mM UDP-galactose in addition to the above components. Distal Kdo-transferase assays contained all the galactosyltransferase reaction components plus 2 mM Kdo, 5 mM CTP, 10 mM MgCl 2 , and 1.8 milliunits of partially purified CMP-Kdo synthase per 10 l. CMP-Kdo is generated in situ because of its short half-life (minutes) (30).…”
Section: Methodsmentioning
confidence: 99%
“…The labeled lipid IV A was converted to Kdo 2 -[4Ј-32 P]lipid IV A using purified E. coli Kdo-transferase (30,31). The products were purified by preparative thin layer chromatography and stored at Ϫ20°C as an aqueous dispersion (30,31). Prior to each use, these substrates were subjected to ultrasonic irradiation in a water bath for 60 s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation